Clitic phenomena in European languages - Beukema, F. H. (Frits H.); Dikken, Marcel den, 1965-; Workshop on "Clitic Phenomena in English and Other European Languages" (1997 : Lajos Kossuth University) (Philadelphia : J. Benjamins, 2000)
This book is concerned with a number of central issues in the theory of clitics, a topic that has become much debated in recent years. Mainly written within a recent generative framework, its contrastive approach discusses these issues against the backgro.
Direct Object Clitic Doubling in Albanian and Greek -- Where do Clitics Cluster? -- Clitic Doubling Constructions in Balkan-Slavic Languages -- On Clitic Sites -- Subject Index -- The Series LINGUISTIK AKTUELL/LINGUISTICS TODAY.
Rev. papers first presented at the Workshop on "Clitic Phenomena in English and Other European Languages," which was held during the Fourth Conference of the European Society for the Study of English, Sept. 5-9, 1997, at Lajos Kossuth University in Debrecen, Hungary; with one additional contribution
Includes bibliographical references and index.
Papers in English, with examples in various languages.
Print version record.
eBooks on EBSCOhost
Keywords: Europe -- Languages -- Clitics; Europe -- Languages -- Clitics -- Congresses; Europe -- Langues -- Clitiques -- Congrès.; Europe -- Langues -- Clitiques; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Syntax; Europe; Clitische elementen; Generatieve grammatica; Conference papers and proceedings